Ochrobactrum anthropi septic arthritis: case report and implications in orthopedic infections - Carla C. Saveli; Marilyn Levi; John Koeppe (MDPI AG, 2010)
Ochrobactrum anthropi is a rare cause of orthopedic infections. We report the second case of Ochrobactrum anthrop septic arthritis in the literature. Our case highlights the ability of Ochrobactrum anthropi to cause septic arthritis and its relevance in the field of orthopedic infections.